if p(x) =x³+3x²-2x+4 then find the value of p(-3)+p(1)+p(0)
Answers
Answered by
9
✔✔heya here is ur answer!!
THANK YOU ✌✌
HOPE IT HELPS YOU ☺☺
THANK YOU ✌✌
HOPE IT HELPS YOU ☺☺
Attachments:
![](https://hi-static.z-dn.net/files/dd7/62bd3fb5a7fa67ec13d01413e272e766.jpg)
DevilDoll12:
There's a mistake
Answered by
4
Heya!
--------
==========================================================
♦Polynomials♦
===========================================================
➰p ( x ) = x³ + 3x² - 2x + 4
=> p ( -3)
◾ (-3)³ + 3 (-3)² - 2 (-3) + 4
=> -27 + 3× 9 + 6 + 4
=> -27 + 27 + 10
=> 10 ✔
=> p (1)
◾ (1)³ + 3(1)² - 2(1) + 4
◾ 1 + 3 - 2 + 4
◾ 4 + 4 - 2
=> 6 ✔
=> p (0)
=> (0)³ + 3(0)² - 2× 0 + 4
=> 4✔
♦Now, p ( -3 ) + p (1) + p (0)
=> 10 + 6 + 4
=> 20 ✔
======================================================
--------
==========================================================
♦Polynomials♦
===========================================================
➰p ( x ) = x³ + 3x² - 2x + 4
=> p ( -3)
◾ (-3)³ + 3 (-3)² - 2 (-3) + 4
=> -27 + 3× 9 + 6 + 4
=> -27 + 27 + 10
=> 10 ✔
=> p (1)
◾ (1)³ + 3(1)² - 2(1) + 4
◾ 1 + 3 - 2 + 4
◾ 4 + 4 - 2
=> 6 ✔
=> p (0)
=> (0)³ + 3(0)² - 2× 0 + 4
=> 4✔
♦Now, p ( -3 ) + p (1) + p (0)
=> 10 + 6 + 4
=> 20 ✔
======================================================
Similar questions